Study on Synthesis and Service Properties of Anticoagulant Ice Microcapsule Coating Material - Rong Chang; Jie Wang; Yongchun Qin; Jian Xu; Wei Zeng; Yange Zhang; Peng Wang (Advances in Materials Science and Engineering)
The presence of ice and snow on a road surface in winter will reduce the traffic capacity of the road network, which can easily lead to traffic accidents. In this study, nonchlorine organic snow-melting salt was added to emulsified asphalt to prepare an anticoagulant ice fog seal. Considering the destructive effect of snow-melting salt on the stability of emulsified asphalt, polyvinyl alcohol was used as an encapsulation material to form a stable two-phase system by mixing snow-melting salt with emulsified asphalt. The zeta potential method was used to test the storage stability of the encapsulated salt solution. The results showed that the material and content of the encapsulation had a significant effect on the stability of the emulsified asphalt and the reduction in the freezing point of the encapsulated salt solution. PVA (1.5%) mixed with 24% sodium acetate was used to prepare an encapsulated salt emulsion, which was mixed with anionic emulsified asphalt and sprayed on the road surface. This significantly reduced the freezing point of road surface water. The recommended spraying dosage of the anticoagulant ice fog seal layer was 0.4 kg/m2, which could lower the freezing point by at least −8°C while simultaneously meeting the antislip performance condition. This was shown to be a preventive maintenance technology with both anticoagulant ice and maintenance effects.